Stability and safety of ships. - Kobylinski, Lech K. (Elsevier ocean engineering book series, 2003)
A stability accident is one of the worst things that can happen to a ship. This two-volume set is intended for those concerned with the prevention against capsizing. It focuses on the regulatory, operational aspects of intact stability, and provides a review of research and results in the field.